Programa Mais Médicos para o Brasil: uma análise sobre experiências de supervisão acadêmica - Ferracuti, Roberta (2019)
From the 1990s, there was a movement to expand the Brazilian population's access to health care, mainly through basic care, and the Family Health Strategy is a proposal adopted by the Brazilian government as a way of reorganizing the health system. Unfortunately, most of the Brazilian municipalities encountered many difficulties during their implementation, ranging from infrastructure to lack of professionals, mainly physicians. In this scenario, the Mais Médicos Program in Brazil was launched in 2013 as a proposal to advance the solution of Primary Health Care (PHC) problems in the SUS, with measures that intervene in the training, structure and provision of physicians in health services. APS. To follow up these new doctors, we have the tutor and the academic supervisor, medical professionals indicated by the Supervisory Institutions linked to the Ministry of Education. Academic supervision is one of the educational axes of the Project, and should develop permanent education processes, guided by the perspective of the teaching-service integration, in the assistance component of the training of the doctors participating in the project. For a better understanding of the supervision process, this analytical and qualitative approach was developed, with semi-structured interviews for Project supervisors. The focus is the understanding and repercussions of the supervision process as a whole, identifying difficulties, potentialities and contributions in the qualification of the medical professional. Among the results, we highlight the importance of the understanding of all involved in the supervision process (supervisors, doctors, their respective teams and managers) about the fact that academic supervision is not a mere supervision, but an instrument of continuous training. The supervisor, as an interlocutor of this process, has the opportunity to provide space for dialogue, exchange of experiences, assistance in creating care protocols and training. The proposal is a review of the academic oversight model of the Mais Médicos Project for Brazil, which may be used in other professional qualification and continuing education projects.